Balanced operation strategies of district heating systems based on dynamic hydraulic-thermal modeling - Xiaojie Lin; Ning Zhang; Zheng Luo; Encheng Feng; Wei Zhong (Energy and Built Environment)
As the improvement of district heating systems, the fine-tuning of operational equipment has become a promising direction. However, in the practical district heating systems, relying solely on manual control and the existing basic models, the dynamic hydraulic-thermal process is hard to cover. Consequently, the primary side control in the current district heating system mainly results in the over or under-supply of heating substations. This article constructs a dynamic hydraulic-thermal model and performs a balanced operation strategies optimization based on the hydraulic-thermal model. The linearization and iterative optimization process are adopted to simplify the hydraulic and thermal modeling for the single pipe, and the hydraulic and thermal calculation are conducted sequentially. For the primary side network in the various operation conditions, the dynamic hydraulic-thermal model is established. The heating supply imbalance of the primary side return temperatures among different heating substations is defined and optimized based on the dynamic hydraulic-thermal model and the particle swarm optimization algorithm. In the case analysis, the results of heating supply imbalance before and after optimization are 0.81 K and 0.47 K, respectively, with a 42.0 % reduction in heating imbalances after optimization. The proposed method could contribute to the fine-tuning of heating substations and the reduction of energy waste due to the imbalanced heating supply, which is significant for the operation strategies of district heating systems.